Simple and highly sensitive 2-hydroxy-1,4-naphthoquinone/glassy carbon sensor for the electrochemical detection of [Ni(CN)4]2− in metallurgical industry wastewater - Cardenas-Riojas, Andy A.; Muedas-Taipe, Golfer; La Rosa-Toro, Adolfo; Sotomayor, Maria D. P. T. [UNESP]; Ponce-Vargas, Miguel; Baena-Moncada, Angélica M. (Springer Nature, 2022)
The pollution generated by the metallurgical industry effluents represents a serious issue for human health and the environment where the presence of cyanide species is particularly dangerous even at low concentration. In this context, we have developed an electrochemical sensor based on a glassy carbon (GC) electrode modified with 2-hydroxy-1,4-naphthoquinone (HNFQ) for the detection of the [Ni(CN)4](aq)2- complex ion from galvanic wastewater. It was characterized by physicochemical techniques such as Raman spectroscopy, electrochemical spectroscopy impedance, and UV–Visible spectroscopy. The electrochemical detection of the complex ion [Ni(CN)4](aq)2- was carried out by the square-wave voltammetry electrochemical technique. The GC/HNFQ electrochemical sensor features a wide linear range of 1.28 × 10–5–1.63 × 10–3 mol L−1 with a determination coefficient R2 of 0.9993, a limit of detection (LOD) of 3.31 ± 2.21 µmol L−1, and a limit of quantification (LOQ) of 10.93 ± 7.31 µmol L−1. Moreover, the proposed sensor displays excellent selectivity to the interfering ions (K +, Na +, Cl -, NO3-, SO42-, and HCO3-). Finally, in order to investigate the molecular interplay between the involved species at the electrode-solution interface, a computational study in the framework of DFT has been conducted, which suggests a parallel orientation of a formed Ni(II)-bis(2-hydroxy-1,4-naphthoquinonate) complex and a graphitic domain of the glassy carbon surface. Graphical abstract: [Figure not available: see fulltext.]
Keywords: 2-Hydroxy-1,4-naphthoquinone; Adsorption; DFT; Electrochemical sensor; Glassy carbon; [Ni(CN)4]2-aq